The Influence of Emotional Intelligence, Work Motivation, and Training on Teacher Performance - Nurmaya Junilasari (Al-Qalam Institue, 2026)
The rapid transformation of the educational landscape requires teachers to continuously adapt emotionally, motivationally, and professionally in performing their roles. This study aims to examine the influence of emotional intelligence, work motivation, and training on teacher performance in an integrated Islamic primary school context. Employing an associative quantitative approach with a survey method, this study involved all 44 teachers as respondents using a total sampling technique. Data were collected through a five-point Likert-scale questionnaire and analyzed using multiple regression analysis. The results indicate that emotional intelligence and work motivation have positive but statistically insignificant effects on teacher performance, while training has a positive and significant influence on improving teacher performance. Simultaneously, emotional intelligence, work motivation, and training collectively contribute significantly to teacher performance. These findings imply that although emotional and motivational factors remain important psychological foundations for teachers, continuous and well-structured training plays a more decisive role in enhancing teacher performance. Therefore, educational institutions are encouraged to prioritize sustainable professional development programs while simultaneously fostering teachers’ emotional intelligence and work motivation to improve instructional effectiveness.